(untitled) (DIMENSI: Journal of Architecture and Built Environment, 2005)
More than two decades, after the emerging of post- modern architecture, the split between construction technology and cultural expression in architecture appeared to become wider and wider. With the exception of a few "high-tech" buildings, the unity of art and applied science (technology) in design seems facing challenges. It is interesting to see how fast and unexpectedly the situation has changed. Many factors and people played a role in this reversal, many new buildings demonstrate that utilitarian artifacts do not have to be oppressive to creativity but can evoke new innovation. One of the most significant contributors was JIN MAO TOWER at Shanghai, China. The paper analyses this building as a genuine synthesis of rational intelligence with art poetry that is still possible. Abstract in Bahasa Indonesia : Lebih dari dua dekade setelah timbulnya arsitektur pasca modern, pemisahan antara tekknologi konstruksi dan ekspresi kultural dalam arsitektur menjadi semakin lebar. Dengan perkecualian beberapa gedung "high-tech", kesatuan antara seni dan teknologi dalam tahap desain terlihat menghadapi tantangan tantangan. Tetapi menarik untuk diamati bahwa situasi telah berubah. Banyak faktor dan tokoh tokoh arsitek memegang peranan penting dalam perubahan ini, banyak bangunan bangunan baru mendemontrasikan bahwa artefak fungsionil tidak bearti menindas kreativitas namun dapat membangkitkan inovasi baru. Salah satu kontributor yang sangat penting adalah JIN MAO TOWER di Shanghai-China. Makalah ini membahas bangunan tersebut sebagai sintesis orijinal yang masih memungkinkan antara kecerdasan rasional dengan puisi seni arsitektur. Kata kunci: Sintesis.